Catalytic combustion of toluene with Pd/La0.8Ce0.2MnO3 supported on different zeolites. Issue 1 (11th June 2017) - Wang, Yongqiang; Xiao, Li; Zhao, Chaocheng; Liu, Fang; Li, Shi
Abstract : Pd/La0.8 Ce0.2 MnO3 catalysts supported on various kinds of zeolites (ZSM‐5, MOR, NaY, and β) were prepared by incipient wetness impregnation method, and these catalysts were investigated by Brunauer‐Emmett‐Teller, X‐ray diffraction analysis (XRD), Fourier transform infrared spectroscopy, and H2 ‐temperature programmed reduction. The catalytic activity of these catalysts was tested for toluene catalytic combustion, and the support effect was investigated. It was found that the ZSM‐5 is the best support than other zeolites (MOR, NaY, and β), because it processes the higher acidity and reducibility, although its specific surface area is smaller than the others. Result of XRD indicates that Pd species are highly dispersed on the surface of the catalysts, and the doping of Pd could greatly improve the activity of La0.8 Ce0.2 MnO3, the light‐off and complete conversion temperature of Pd/La0.8 Ce0.2 MnO3 /ZSM‐5 are only 112 and 227°C, respectively. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 215–220, 2018